Free electron lasers driven by plasma accelerators: status and near-term prospects. (10th September 2021) - Emma, C.; Van Tilborg, J.; Assmann, R.; Barber, S.; Cianchi, A.; Corde, S.; Couprie, M. E.; D'Arcy, R.; Ferrario, M.; Habib, A. F.; Hidding, B.; Hogan, M. J.; et al.
Abstract: Owing to their ultra-high accelerating gradients, combined with injection inside micrometer-scale accelerating wakefield buckets, plasma-based accelerators hold great potential to drive a new generation of free-electron lasers (FELs). Indeed, the first demonstration of plasma-driven FEL gain was reported recently, representing a major milestone for the field. Several groups around the world are pursuing these novel light sources, with methodology varying in the use of wakefield driver (laser-driven or beam-driven), plasma structure, phase-space manipulation, beamline design, and undulator technology, among others. This paper presents our best attempt to provide a comprehensive overview of the global community efforts towards plasma-based FEL research and development.